Antimicrobial resistance characterization of Staphylococcus aureus from different animal food origins in Jimma, South Western Ethiopia - Diriba Taddese; Mukarim Abdurahaman; Motuma Debelo; Eshetu Shumi; Gelana Urgessa; Dase Kefyalew; Moa Melaku; Tadele Kebeta; Gazali Abafaji (Discover Food, 2025)
Abstract Antimicrobial resistance in Staphylococcus aureus poses a significant global health threat. This study aimed to investigate the prevalence and antimicrobial resistance patterns of S. aureus isolated from various animal food sources in the Jimma zone of Ethiopia. Samples were collected during a cross-sectional study conducted between 2022 and 2023, encompassing milk, beef, eggs, and cheese.Samples were collected from foods of animal origin, including milk, beef, eggs, and cheese. The food samples were processed and cultured on selective media. The isolated organisms were identified by biochemical tests and subjected to antimicrobial susceptibility testing. Out of a total of 480 animal foods analyzed, the overall prevalence of Staphylococcus aureus was recorded in 41 (8.54%). Among the 96 samples from each source, the highest prevalence was found in beef and milk (12.5% each), followed by eggshells (9.4%), cheese (6.3%), and egg-content samples (2.1%). Kanamycin and tetracycline exhibited the highest resistance rates among the isolates, with 39.0% and 36.6% resistance, respectively. The least antibiotic resistance was observed against cefoxitin (7.3%). Ciprofloxacin, trimethoprim and ceftaroline showed resistance in 14.6% of the isolates. Resistance to imipenem was not detected in this study isolates. Nearly a quarter (24.4%) of the 41 Staphylococcus aureus isolates exhibited multi-drug resistance, highlighting the significant prevalence of this concerning trait. In particular, milk samples had the highest number of multidrug-resistant isolates. This study highlights the prevalence of Staphylococcus aureus in different food samples of animal origin and reveals the level of antimicrobial resistance. These findings emphasize the importance of food safety measures, responsible use of antibiotics, and continuous monitoring of antimicrobial resistance in animal feed.